Etnomatematika pada perlengkapan tari bagipang masyarakat Pantai Hambawang Timur - Sarmina Dewi; Abdul Jabar; Rahmita Yuliana Gazali (STKIP PGRI Banjarmasin, 2019)
One of the traditional cultural dances of society Pantai Hambawang Timur is bagipang dance. Bagipang dance is a genetic inheritance that needs to preserve. This dance performance uses a piggyback made of bamboo with distinctive make-up and fashion, and accompanied by gamelan music. The purpose of this research is to know the forms and mathematical concepts that exist in bagipang dance equipment, and this research method is qualitative with an ethnographic approach. The result of the study shows that there are regular geometric shapes, that is: (1) rectangles; (2) rhombus; (3) trapezoid with isosceles; (4) equilateral triangles and isosceles; (5) circles; (6) sphere; and (7) half sphere, there was something irregular in the shape of the gypsy horse. There are mathematical concepts in bagipang dance equipment, that is: (1) numbers; (2) constant function; (3) periodic function; (4) reflection ; (5) set; (6) volume of rotary object; (7) volume measurement in liters; (8) volume with glass units; and (9) volume of cones with glass units. One example of a mathematical concept is the concept of numbers. The numbers we know are zero, one, two, three, four, five six, seven, eight, nine. While a number is an arrangement of numbers that have a specific value. Numbers consist of one number we know by unit, the two numbers we know with tens, three numbers that we know by hundreds, and so on.